Coronavirus disease 2019 (COVID-19) in special groups: A single-center experience in sickle cell disease patients in Saudi Arabia - Rehab Y Al-Ansari; Leena M Abdalla; Yasmin A Qomawi; Laila J Alromaih; Mohanad O Bakkar; Amal S Shilash; Nawaf Y Zakary (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Sickle cell disease (SCD) is a group of hereditary diseases, inherited as autosomal recessive disorder, which causes mutation in the β-globin gene. As a result, there is a change in the sixth amino acid from glutamic acid to valine. The affected red blood cell is then prone to polymerization and sickling crisis under conditions of low oxygen tension. One of the major causes of mortality in SCD is acute chest syndrome (ACS). On the other hand, coronavirus disease 2019 (COVID-19) is a pandemic disease that carries significant mortality and morbidity worldwide with unknown outcomes in the affected SCD population. This study was created for that reason. MATERIALS AND METHODS: We report a case series of ten SCD patients who were affected by COVID-19 and required admission between May 1, 2020, and October 30, 2020, at a tertiary care hospital in Dhahran, eastern region of Saudi Arabia. Historical data were obtained retrospectively from electronic records. MS Excel was used for data entry, and SPSS version 23 was used for data analysis. RESULTS: The mean age of the patients involved in the study was 32 years, and the mean duration of symptoms was 5.7 days. None required critical care admission, and there was no mortality. All patients were discharged from hospital in good condition with no requirement of home oxygen. CONCLUSION: Although we expected a fatal outcome of SCD patients affected by COVID-19 infection, our limited case series showed favorable disease behavior and outcome, with a suspicion of underlying unclear protective mechanism from serious complications. However, further studies are required to better understand COVID-19 behavior in SCD patients.